2020
DOI: 10.1136/bmjopen-2020-036916
|View full text |Cite
|
Sign up to set email alerts
|

Occupational justice and social inclusion among people living with HIV and people with mental illness: a scoping review

Abstract: ObjectiveTo explore ways in which occupational justice and social inclusion are conceptualised, defined and operationalised in highly stigmatised and chronic conditions of mental illness and HIV.DesignThis scoping review protocol followed Arksey and O’Malley’s (2005) Scoping Review Framework.Data sources and eligibilityThe following databases were searched for the period January 1997 to January 2019: Medline via PubMed, Scopus, Academic Search Premier, Cumulative Index to Nursing and Allied Health Literature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…A possible explanation is that individuals with SUDs or with substance use history are perceived more negatively as weak moral character, lacked capacity, dishonest, and reduced social inclusion, which lead to not engaged in community events, including employment. [ 21 34 35 ] These may impact an individual's access to employment opportunities or employer's hiring decisions. [ 36 ] Then, consequently contributes to a further increase in stigma internalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that individuals with SUDs or with substance use history are perceived more negatively as weak moral character, lacked capacity, dishonest, and reduced social inclusion, which lead to not engaged in community events, including employment. [ 21 34 35 ] These may impact an individual's access to employment opportunities or employer's hiring decisions. [ 36 ] Then, consequently contributes to a further increase in stigma internalization.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] If unemployed people with low social inclusion, they are less social interaction, less acceptance, and more perceived stigma. [ 35 37 ] Some studies indicated that substance user who are unemployed or did not regularly go to work may be less socially included than full-time working people. Thus, substance users who are unemployed with a reduced social inclusion are more likely to report higher levels of perceived stigma.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review is suggested due to the breadth of information required to gain a broad understanding of the nature of the evidence and policy relating to substance use and SUDs in Zimbabwe. In developing the protocol, the framework developed by Arksey and O’Malley [20] together with relevant previous applications of this framework, for example, [21, 22] were consulted. Ethics approval was waived by the De Montfort University Faculty of Health and Life Sciences Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…In these disruptions, occupational transitions are an important concept to explore, regarding how people adapt and adjust to change. Successful negotiation of life changes needs to be occupation-based (Nhunzvi et al, 2020) strategically positioning occupational therapy for a significant role in facilitating recovery from the COVID-19 pandemic.…”
Section: Introduction and Background Literaturementioning
confidence: 99%